Mechanisms of cancer pain - Haroun, Rayan; Wood, John N; Sikandar, Shafaq (Frontiers in Pain Research, 2023)
Personalised and targeted interventions have revolutionised cancer treatment and dramatically improved survival rates in recent decades. Nonetheless, effective pain management remains a problem for patients diagnosed with cancer, who continue to suffer from the painful side effects of cancer itself, as well as treatments for the disease. This problem of cancer pain will continue to grow with an ageing population and the rapid advent of more effective therapeutics to treat the disease. Current pain management guidelines from the World Health Organisation are generalised for different pain severities, but fail to address the heterogeneity of mechanisms in patients with varying cancer types, stages of disease and treatment plans. Pain is the most common complaint leading to emergency unit visits by patients with cancer and over one-third of patients that have been diagnosed with cancer will experience under-treated pain. This review summarises preclinical models of cancer pain states, with a particular focus on cancer-induced bone pain and chemotherapy-associated pain. We provide an overview of how preclinical models can recapitulate aspects of pain and sensory dysfunction that is observed in patients with persistent cancer-induced bone pain or neuropathic pain following chemotherapy. Peripheral and central nervous system mechanisms of cancer pain are discussed, along with key cellular and molecular mediators that have been highlighted in animal models of cancer pain. These include interactions between neuronal cells, cancer cells and non-neuronal cells in the tumour microenvironment. Therapeutic targets beyond opioid-based management are reviewed for the treatment of cancer pain.